A phase ib clinical trial of oral ciprofloxacin and etoposide in subjects with resistant acute myeloid leukemia - Gera, Kriti; Cline, Christina; Al-Mansour, Zeina; Medvec, Andrew; Lee, Ji-Hyun; Galochkina, Zhanna; Hsu, Jack; Hiemenz, John; Farhadfar, Nosha; Dean, Erin A.; Wingard, John R.; Brown, Randy (Leukemia & lymphoma, 2024)
A phase 1b study was conducted to evaluate the safety and feasibility of ciprofloxacin and etoposide combination treatment in subjects with relapsed and refractory acute myeloid leukemia. Eleven subjects were enrolled in the study. Utilizing the standard '3 + 3' design, escalating ciprofloxacin doses (750 mg, 1000 mg) twice daily on D1-D10 in combination with a fixed dose (200 mg) of etoposide on D2-D8 were administered. Maximum tolerated dose was determined to be 1000 mg of ciprofloxacin in combination with 200 mg of etoposide. Serious adverse events occurred in 54.5% ( = 6) subjects and 91% ( = 10) subjects reported ≥ grade 3 toxicities. Nine subjects completed treatment, one had a dose-limiting toxicity, and one withdrew. One subject achieved complete remission with a duration of 111 days and one subject achieved morphologic leukemia-free state after cycle 1. While the combination demonstrated safety and an acceptable toxicity profile, only modest hematologic and clinical benefits were observed.This trial was registered at www.clinicaltrials.gov as #NCT02773732.